Embedding spatial analyses in culture-historical discourse. Experiences from Jordan and Cyprus - Kennedy , Will M. (Journal of Greek Archaeology, 2024)
Before discussing specific case studies, some general remarks on the application of computer-based, spatial analytical methods within landscape archaeological research seem appropriate. Particularly, the underlying understanding of the term ‘landscape archaeology’ must be clarified, which is often only very vaguely defined. As landscape archaeology has grown increasingly en vogue in recent years, a universally valid definition remains elusive. Serving ‘[…] as an envelope for anything […]’, landscape archaeology continues to act as ‘[…] a reasonable umbrella term for all research in the social construction of space’. However, one consensus seems to understand it not merely as an environmental archaeology which is only concerned with the physical landscape, but – importantly – also as an approach that studies the meaningfulness of landscapes for past human societies, and the interactive role of landscapes and human activities through time. Considering landscapes both as a ‘product of natural features’ as well as ‘the result of human actions’, it becomes clear that past peoples lie at the centre of landscape archaeology. Although distinctly interdisciplinary, its core is therefore deeply rooted in the humanities, aiming at researching past human-environmental relations on the basis of material culture within its natural environmental context. Landscape archaeological studies research the genesis of cultural landscapes (Kulturlandschaftsgenese), i.e. all forms of natural landscape changes that were caused or influenced (by) humans, from a distinctly archaeological, material-based perspective. In addition to traditional archaeological research of material remains (i.e. archaeological surveys, excavations, detailed material studies), landscape archaeological studies employ different methods from (a) other disciplines of the humanities (e.g. ancient history, epigraphy or numismatics), (b) the natural and geosciences (e.g. geography, biology or ecology), as well as (c) computer sciences, including remote sensing methodologies, spatial statistics and other computer-based spatial analyses.